A novel electric pulse pathway to suppress plastic localization and enhance strain hardening of medium Mn steel. (December 2022) - Hu, Bin; Wen, Qinghua; Guo, Qinyi; Wang, Yongjin; Sui, Han; Luo, Haiwen
Abstract: Pulsed electric current (PEC) treatments with current density up to 30 A/mm 2 were applied on an intercritically annealed medium Mn steel (MMS). We found that the PEC treatment at 15 A/mm 2 promoted the significant transformation of some coarse-sized austenite grains to martensite (α') together with the partition of C into remaining austenite, resembling the quenching & partitioning treatment. Such a pulsed current induced martensite transformation (PCIMT) is primarily attributed to the athermal effect of pulsed current that could increase the Ms point of austenite to a temperature higher than the temperature rise caused by Joule heat. This not only refined the austenite grains but also enhanced their mechanical stability; moreover, it also led to both reduced quantity of ferrite(α)/austenite(γ) interfaces and geometry necessary dislocations (GNDs) generated near the α/α' and γ/α' interfaces. Consequently, the PEC treated specimens exhibit more prominent strain hardening with suppressed strain localization than the non-PEC-treated one. Graphical abstract: Image, graphical abstract